Structure and magnetic state of films deposited by laser sputtering of nickel - Bagmut, A.G.; Shipkova, I.G.; Zhuchkov, V.A. (Functional Materials, 2009)
The influence of annealing on structure and phase states of nickel laser condensates has been studied. Volume changes, orientation relations between HCP and FCC crystal lattices, and magnetic properties changes after annealing are established. It has been shown that on (001) KCl substrate at a temperature higher than 400 K, a two-positioned nucleation and growth of HCP Ni grains takes place. Both positions contain groups of crystals with zone axes [111] and [221] perpendicular to the substrate. The annealing of film initiates polymorphic HCP -> FCC transformation accompanied by relative increasing of the material density by 18.5 %. The polymorphic transformation results in a change of the film magnetic characteristics: the film gets a magnetic moment, and hysteresis is observed at magnetic reversal.